2018
DOI: 10.1016/j.heares.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The endocochlear potential as an indicator of reticular lamina integrity after noise exposure in mice

Abstract: The endocochlear potential (EP) provides part of the electrochemical drive for sound-driven currents through cochlear hair cells. Intense noise exposure (110 dB SPL, 2 h) differentially affects the EP in three inbred mouse strains (C57BL/6 [B6], CBA/J [CBA], BALB/cJ [BALB]) (Ohlemiller and Gagnon, 2007, Hearing Research 224:34–50; Ohlemiller et al., 2011, JARO 12:45–58). At least for mice older than 3 mos, B6 mice are unaffected, CBA mice show temporary EP reduction, and BALB mice may show temporary or permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
2
8
1
Order By: Relevance
“…Our findings of noise-induced acute stress response in the lateral wall of CBA, but not B6 mice correspond to previous studies showing an acute EP drop in noiseexposed CBA mice exclusively (Wang et al 2002;Hirose and Liberman 2003;Ohlemiller and Gagnon 2007;Ohlemiller et al 2018). The question is then whether the acute stress response/EP drop axis is linked with the observed heightened noise vulnerability of OHCs of CBA mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings of noise-induced acute stress response in the lateral wall of CBA, but not B6 mice correspond to previous studies showing an acute EP drop in noiseexposed CBA mice exclusively (Wang et al 2002;Hirose and Liberman 2003;Ohlemiller and Gagnon 2007;Ohlemiller et al 2018). The question is then whether the acute stress response/EP drop axis is linked with the observed heightened noise vulnerability of OHCs of CBA mice.…”
Section: Discussionsupporting
confidence: 89%
“…However, this possibility is still to be directly shown by relevant mutant mouse models. It is to be noted that a recent study suggested that lateral wall pathology drives OHC loss particularly in young adult CBA mice, which were also used in the current study, while older CBA mice are less affected (Ohlemiller et al 2018).…”
Section: Discussionmentioning
confidence: 90%
“…The changes seen in marginal cells may depend on the strain examined. A recent report showed that noise-exposed CBA/J mice results in temporary EP reduction, while the same is not true for C57B6 mice (Ohlemiller et al 2018). Therefore, the strial effects of noise in the present findings may be characteristic for CBA/J mice but not of some other strains.…”
Section: Fig 8 Noise-diminished Immunolabeling For Kcnq4 In Ohcs Iscontrasting
confidence: 63%
“…The EP is a biopotential within scala media (~+ 100 mV) that complements the negative membrane potential of the hair cells to provide the driving force for outer hair cell forward and reverse transduction [36,37]. Many studies, using guinea pigs or mice, have shown that the much higher noise levels than those used in the present study are required to cause a sustained drop in EP (~98 dB SPL; [38][39][40][41][42][43][44][45]). Moreover, Hirose and Liberman [45] showed that despite a temporary threshold shift of 40 dB after 94 dB SPL noise exposure for 2 h, the EP was unaffected in CBA/CaJ mice.…”
Section: Discussionmentioning
confidence: 83%